THE VISION FOR THE NEXT GENERATION OF AIR TRAFFIC MANAGEMENT SYSTEMS - Kharchenko, Volodymyr; Chynchenko, Yuriy (Proceedings of National Aviation University (archive), 2006)
The introduction of contemporary Next Generation Air Transportation System (USA) and SESAR – the New Generation of Air Traffic Management Systems in Europe is considered.